Job training programs for youth in low-income countries - Jonathan Stöterau (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2019)
* Skills training programs - one of the most widely used labor market interventions worldwide - have been criticized recently to lack cost-effectiveness. * Job training programs differ from pure skills trainings: they combine multiple services to address the specific constraints and opportunities for youth. * Newly available evaluation studies suggest that such programs can have large impacts in low-income countries. * Two features of low-income countries need to be reflected in program design and success measurement: extremely low skill levels and inexistent wage-employment opportunities. * In addition, successful programs commonly include (i) incentives for training providers, (ii) financial support for participants, and (iii) gender considerations.
Keywords: 330